Defining the Existence of Housing Submarkets for Terraced Properties in Johor Bahru - Wen Xin, Wendy Lim; Burhan, Burhaida; Mohd Diah, Mohd Lizam (International Journal of Sustainable Construction Engineering and Technology, 2024)
Recent research on housing submarkets over the decades and the necessity to categorise heterogeneous property markets into distinct submarkets are deemed essential in the real estate field. Housing submarkets operate based on the concept of a group of dwellings that are substantially close substitutes to one another, but are relatively poor substitutes for dwellings in different submarkets. This mechanism primarily depends on spatial variations in housing characteristics related to structure, location, and neighbourhood. Housing submarkets are vital in enhancing the precision of housing pricing and analysing the dynamic shifts in the property markets. This study aimed to define and examine the presence of housing submarkets for the terraced properties in Johor Bahru with the Malaysian Valuation and Property Services Department (JPPH) housing transaction database. The database documented 63,036 housing transactions between 2009 and 2018 with thirteen independent structural and locational housing attributes. The study also recommended an objective data-driven methodology by integrating principal component analysis (PCA) and cluster analysis to delineate housing submarkets. Resultantly, the presence of housing submarkets was identified within the property market with the delineation of two specific submarket effects, namely the housing location cluster and housing quality cluster. The submarkets provided a comprehensive framework for segregating property traits into prospective clusters. Establishing housing submarkets may provide valuable insights, implicit cluster details, and a more reliable hedonic price model prediction. The outcomes could be employed by property valuers, analysts, and urban planners for a sound comprehension of current real estate circumstances.